2021
DOI: 10.5534/wjmh.200181
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cited Articles in the Field of Male Infertility and Antioxidants: A Scientometric Analysis

Abstract: Purpose The objective of this scientometric analysis was to recognize the top 100 cited articles on ‘Male infertility and Antioxidants’ and analyze its publication characteristics. Materials and Methods The Scopus database was used to retrieve related articles and the top 100 identified based on citation rate. Results The articles were published in 56 journals between 1995 and 2019 with a median (interquartile range) citation score of 17 (5–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition, numerous scientometric studies have identified Ashok Agarwal as the key contributor to male infertility research. He covered topics such as sperm DNA fragmentation [ 16 ], varicocele [ 17 ], and oxidative stress [ 18 ] in male infertility, as well as the effects of antioxidants [ 19 ], androgen replacement therapy [ 20 ], and innovative tools such as proteomics [ 21 ] for male infertility investigation and management. Furthermore, Agarwal, Ashok's H-index was 101, highlighting his notable influence in the lots of fields relative to other authors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous scientometric studies have identified Ashok Agarwal as the key contributor to male infertility research. He covered topics such as sperm DNA fragmentation [ 16 ], varicocele [ 17 ], and oxidative stress [ 18 ] in male infertility, as well as the effects of antioxidants [ 19 ], androgen replacement therapy [ 20 ], and innovative tools such as proteomics [ 21 ] for male infertility investigation and management. Furthermore, Agarwal, Ashok's H-index was 101, highlighting his notable influence in the lots of fields relative to other authors.…”
Section: Discussionmentioning
confidence: 99%